Seroprevalence and Current Infections of Canine Vector-Borne Diseases in Costa Rica - Springer, Andrea; Montenegro, Víctor M.; Schicht, Sabine; Globokar Vrohvec, Majda; Pantchev, Nikola; Balzer, Jörg; Strube, Christina (Frontiers in Veterinary Science, 2019)
Domestic dogs may carry several vector-borne pathogens, including zoonotic agents, especially in tropical regions like Central America. The epidemiology of these pathogens is prone to change due to urbanization, trade and travel as well as climate change, necessitating repeated monitoring. This study aims to present a comprehensive picture of canine vector-borne diseases in Costa Rica, combining data on seroprevalence with molecular species identification of the causative pathogens. In this survey, 294 dogs from all seven provinces of Costa Rica were included. After a clinical examination, diagnostic blood samples were analysed with regard to packed cell volume (PCV) and presence of microfilaria. Serum samples were tested for antibodies against Ehrlichia spp., Anaplasma spp., Babesia spp., Borrelia burgdorferi sensu lato (s.l.) as well as antigen of Dirofilaria immitis. Seropositive and microfilaremic blood samples were analysed by PCR to detect current infections and identify the pathogen species. Overall, 45.24% (133/294) of dogs were seropositive for at least one of the tested pathogens. Seroprevalence was highest for Ehrlichia spp. (39.46%, 116/294), followed by Babesia spp. (23.13%, 68/294), Anaplasma spp. (13.27%, 39/294) and B. burgdorferi s.l. (0.34%, 1/294). Generalized linear mixed models indicated a significant association of Ehrlichia-, Anaplasma- and Babesia-seropositivity, as well as a significant effect of age and breed on Ehrlichia-seropositivity. Furthermore, a statistically significant negative effect of Ehrlichia-, Anaplasma- and Babesia-seropositivity on PCV was found. Regarding current infections, Ehrlichia canis DNA was detected in 51.72% (60/116) of Ehrlichia-seropositive dogs, while Ehrlichia ewingii and Ehrlichia chaffeensis were not detected. Furthermore, 10.26% (4/39) of Anaplasma-seropositive dogs were coinfected with Anaplasma phagocytophilum and Anaplasma platys, while one animal (2.56%) was infected with A. phagocytophilum only. Among Babesia-seropositive dogs, Babesia vogeli and Hepatozoon canis were detected in one animal each (1.47%, 1/68). Dirofilaria immitis antigen was detected in 4.42% (13/294) of dogs. In microfilaremic animals, D. immitis as well as Acanthocheilonema reconditum infections were identified. This survey demonstrates that canine vector-borne pathogens, including zoonotic agents like A. phagocytophilum and D. immitis, are widespread in Costa Rica. Thus, protection of dogs from disease-transmitting vectors is recommended from an animal welfare as well as public health perspective.